FABRICATION OF POROUS POWDER MATERIALS WITH CONTROLLED DIRECTION FILTERING - V. Kovalevskij; Yu. Alekseev; L. Kerzhenceva; A. Zhuk; A. Kovalevskaja; V. Zhuk (Литьë и металлургия)
The technology for obtaining of porous powder materials with frame structure on the basis of spherical particles of titanium powder, using application of technological coatings of Тi (Si+Мо), (Si+С) or (W+С) was developed. Formation of the powder with the coating was conducted in molding die under the pressure below the flow limit (under 200 MPa). Reaction sintering in a vacuum furnace was carried out at the temperature of 900 оС with the exposure within 1 hour, which allowed receiving penetration factor over 39·10–13 m2 with the formation of powder porous materials with isotropic structure and increased properties.